1990
DOI: 10.1093/ndt/5.11.937
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Arterial Prostaglandin E2 During Haemodialysis

Abstract: The absence of a reduction in peripheral vascular resistance secondary to hypervolaemia leads to so-called volume hypertension. In order to study whether a deficient formation of the vasodilator autacoid prostaglandin E2 (PGE2) contributes to the preservation of inadequate vascular tone during extracellular volume expansion, arterial plasma PGE2 and the stable PGE2 metabolite 13,14-dihydro-15-keto-PGE2 (PGE2-M) were determined in 13 oligoanuric women on chronic haemodialysis. Prior to treatment eight of them h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Nonetheless, it is unknown whether RBCs are capable of liberating PUFA hydroxy metabolites into blood or tissues. Previous studies detected small changes in plasma levels of prostaglandin E2 (PGE2), prostaglandin F2a (PGF2a) [41,42] and 5/12-HETE [43] after hemodialysis. Our data demonstrate that LOX metabolites are exhausted (positive arteriovenous difference) in RBCs that pass through the peripheral tissues, specifically the muscles in the upper limbs, during hemodialysis.…”
Section: Lox/cyp ω/(ω-1)-hydroxylase Metabolitesmentioning
confidence: 99%
“…Nonetheless, it is unknown whether RBCs are capable of liberating PUFA hydroxy metabolites into blood or tissues. Previous studies detected small changes in plasma levels of prostaglandin E2 (PGE2), prostaglandin F2a (PGF2a) [41,42] and 5/12-HETE [43] after hemodialysis. Our data demonstrate that LOX metabolites are exhausted (positive arteriovenous difference) in RBCs that pass through the peripheral tissues, specifically the muscles in the upper limbs, during hemodialysis.…”
Section: Lox/cyp ω/(ω-1)-hydroxylase Metabolitesmentioning
confidence: 99%
“…We have no evidence that hemodialysis affected resolvins, prostaglandins, thromboxanes, or other LOX/CYP ω/(ω-1)-hydroxylase metabolites in our patients (Shelmadine, 2017). Only few studies detected small changes in PGE2 or PGF2a (Losonczy, 1990;Schultze, 1984) and 5/12-HETE levels (Dolegowska, 2012) 4-HDHA is a mediator of antiangiogenic effects of n-3 PUFAs (Sapieha, 2011). Since we found that the majority of LOX metabolites measured were not affected by dialysis, we suggest that these metabolites are unlikely to play important roles in this scenario.…”
Section: Edps/dihdpasmentioning
confidence: 62%